Observer based output feedback control of thrust magnetic bearings - Okur, Beytullah; Zergero?lu, Erkan; Tatlıcıoğlu, Enver; Basaran, Sinan; Sivrioğlu, Selim (Institute of Electrical and Electronics Engineers Inc., 2011)
In this paper, we present an observer based output feedback controller for a thrust magnetic bearing system. A model independent variable structure like observer is used to determine the rotor velocity in order to remove the velocity dependency of the controller. The desired system dynamics have been utilized in the controller design and asymptotic stability of the observer-controller couple is guaranteed via Lyapunov based arguments. Experimental results are presented to illustrate the performance and feasibility of the proposed method. © 2011 IEEE. © 2022 Elsevier B.V., All rights reserved.
2011 50th IEEE Conference on Decision and Control and European Control Conference, CDC-ECC 2011 -- Orlando, FL -- 89653
Keywords: Asymptotic stability; Feedback control; Magnetic bearings; Thrust bearings; Controller designs; Model independent; Observer based output feedbacks; Observer controllers; Observer-based output feedback control; Rotor velocity; System Dynamics; Thrust magnetic bearing; Controllers